ESTUDO SOBRE O CORYNEBACTERIUM DIPHTHERIAE. II - OBSERVAÇOES SOBRE BACILOS DIFTÉRICOS E DIFTERÓIDES ISOLADOS EM SÃO PAULO: ASPECTO MORFOLÓGICO, PROPRIEDADES FERMENTATIVAS, VIRULÊNCIA E FREQUÊNCIA DOS TIPOS DE CORYNEVIBACTERIUM DIPHTHERIAE ENCONTRADOS - Chistovão, Dacio de Almeida (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1957)
Fermentative properties of diphtheriae bacilli are still a controversial subject. This is due to lack of uniformity in the technique employed by several investigators and to the existence or predominance of different varieties of the microorganisms in different areas. The high incidence in São Paulo of saccharose fermenting, virulent strains of O. diphtheriae (up to 35.7 per cent) makes it impossible to differentiate O. diphtheriae from O. xerose by the fermentation of that sugar. This fact led the author to investigate the possibilitby of using dextrin and glycerol in the identification of the organisms. One hundred and ninety three virulent strains of diphtheria bacilli and 129 strains of diphtheroids and avirulent O. diphtheriae were examined for their action on dextrin; 66 virulent strains and 71 diphtheroids and avirulent diphtheria bacilli were investigated in relation to the fermentation of glycerol. Each;train was tested in two culture media, one solid, the other liquid, using appropriate controls. The solid medium furnished better results which are presented in tables II to V, where their distribution is made according to the virulence and morphological aspects of the strain. Virulence was verified through Frazer 's intracutaneous technique in rabbits, which includes a control of the specificity of the positive tests. The data presented reveal clearly, once more, that the morphological aspect by itself is not a sufficient character for the identification of diphtheria bacilli. The virulent .strains studied generally presented a rather characteristic morphology and, in the solid medium, always fermented glucose, dextrin and glycerol. Occasionally, glycerol was fermented only on the fourth day of in cubation. A considerable percentage of these strains also fermented saccharose. This finding, on account of its particular interest, has been the object of a special communication. The results obtained with avirulent O. diphtheriae and diphtheroid strains do not permit definite conclusions, but the following aspects may be pointed out. The majority of these strains, 129 out of 185, were morphologically "not similar" to diphtheria bacilli (table I). However, among strains that fermented both glucose and dextrin, only 26 out of 62 did not show a characteristic morphology (18 GoDS and 8 GoD: table IV). When fermentation of glycerol also occurred besides that of the two forementioned carbohydrates, the proportion of strains morphologically not resembling O. diphtheriae was even smaller, 2 out of 18 (table V, columns GoDSGi and GoDGi). Considering the avirulent strains of corynebacteria that fermented saccharose, it was observed that a small proportion of those fermenting also glucose, dextrin and glycerol showed a "not similar" morphology, whereas the latter characteristic predominated among strains fermenting only saccharose, glucose, and dextrin(table V). No strain unable to ferment glycerol was found among those strains that attacked glucooo and dextrin but which did not ferment saceharose. It seems, threfore, that there ar€ reasons to ascribe diagnostic value to the fermentation of glycerol, besides that of dextrin and glucose. Furthermore, 6 out of 20 strains not fermenting one or two of these three substance (table V) as well as 13 out of 84 strains not fermenting any of the substancrs tried (table IV) were morphologically similar to C. diphtheriae, though none in a typical way (table III). Accordingly, thre are indications that corynebacteria which in the solid medium employed, fail to ferment at least one of the three substances glucose, dextrin and glycerol are very unlikely to be C. diphtheria:e, even when morphologically similar to diphtheria bacilli. Table VI presents the distribution of 151 virulent and 17 avirulent strains of C. diphtheriae according to type, and for the virulent strains, according to action on saccharose. Only 2.4 per cent were classified as belonging to gra1 is type; 54 per cent as gravis-like; 22.6 per cent as mitis-like and 69.6 per cent as mitis. Among the virulent strains, the percentages 0.7, 4.0, 23.2 and 72.2 were found as belonging, respectively, to gravis, gravis-like, mitis-like and mitis types; among the avirulent ones, 17.6, 17.6, 17.6 and 47.1. Tendency to a greater proportion of mitis type among the virulent strains was clearly revealed; such a tendency seems to increase when, among the virulent strains, only the non-saccharose-fermenting strains are considered. Three of the 4 gravis strains were avirulent. The only virulent gravis strain attacked saccharose. Among the virulent strains, it may be seen that saccharose was ferm€nted by 19 (17.4 per cent) out of the 109 belonging to mitis type, by 5 (14 per cent) out of the 35 mitis-like and by 5 out of the 6 gravis-like strains.